Defect passivation and lattice distortion enhance solid-state photoluminescence of two-dimensional perovskites. (16th June 2020) - Zhou, Chenyang; Wang, Chao; Chu, Ya; Ma, Linlin; Liu, Yalan; Zhang, Xiaotao; Yu, Xi; Wang, Haiyuan; Zhao, Guangjiu
Abstract: In this work, we first synthesized a novel solid-state highly efficient photoluminescent (PEA)2 PbBrx Cl4-x /PbCl2 (x = 0, 0.5, 2, 2.5, 3, 4; PEA = C6 H5 C2 H4 NH3 ) system via a cooperative regulation of defect passivation and lattice distortion by combining the interface and crystal engineering. Defect passivation of two-dimensional (2D) perovskite at grain boundary via PbCl2 results in photoluminescence (PL) enhancement and the averaged photoluminescent lifetime increasing by interface engineering. Moreover, structural distortion degree of perovskite octahedron is reduced by doping bromine anion. As a result, PL is tuned from white to blue in the system of (PEA)2 PbBrx Cl4-x /PbCl2 due to the release of lattice distortion via crystal engineering. These results show that the system of (PEA)2 PbBrx Cl4-x /PbCl2 has potential application in optoelectronic devices via cooperative regulation strategy by combining interface and crystal engineering.